A Review on Health Benefits of Indian Spices (International Journal of Innovative Research in Engineering & Management, 2023)
Seed spices are an important category of  agricultural commodities that contribute significantly to our  country's economy. India has long been known as a spice producing country. Coriander, cumin, and fennel are  members of the umbelliferon family, whereas fenugreek  belongs to the Fabaceae family. Bioactive compounds, also  bioactive constituents, are occurs naturally, physiologically  active phytochemicals that operate as a natural defence  mechanism for host plants or have previously been  exploited as medications, perfumes, or taste components.  They're a gold mine of opportunities in our search for useful  bioactive molecules for pharmacotherapy or other wellness  issues. Seed spices affect a number of biological systems,  such as the digestive, circulatory, reproductive, or  neurological systems, causing a range of metabolic but also  physiologic consequences. Antioxidants, antidiabetic,  anticancer, antimicrobial activity, hypolipidemic influence,  insecticidal, beneficial in heavy menstrual bleeding, aiding  digestion, high blood pressure, instrumentation of enzymes  involved, immune function, reduction of inflammatory  process, molecular mechanism, modulations of immune  systems, The purpose of this research is to have a  thorough analysis on the present trends in research here on  health advantages of four common seed seasonings: cumin,  coriander, but also fennel.
Keywords: Antioxidant; Cumin; Coriander; Nutraceuticals; Seed spices